Fortalecimiento de las competencias orales y escritas en un ambiente de aprendizaje con procesos interdisciplinarios, mediado por las TIC y el aprendizaje basado en proyectos (2017)
The present study is a proposal for the development and strengthening of the communicative skills of writing and orality of a group of students in the Departmental Rural Educational Institution (IERD) Andes of the municipality of San Bernardo, Cundinamarca. This study was carried out from the perspective of action research in order to deepen the educational context looking for opportunities for improvement in the teaching and learning processes. It is approached from three phases: diagnostic, design and implementation and evaluation. A reason for this, an atmosphere of interdisciplinary learning supported by Information and Communication Technologies (ICT) and Based Learning Project (BLP) is implemented not only to strengthen oral and written competencies, but also the autonomy, Collaborative Learning, initiative and digital skills of students. As a result, an individual and group progress was evident as it shown in travel designed phases and finished products submitted from the intervention.